Synthesis and Biological Evaluation of Novel Substituted 1,3,4-thiadiazole and 2,6-di aryl substituted imidazo [2,1- b] [1,3,4]thiadiazole Derivatives - Hegde, Gurumurthy; Boodappa, Chandrakantha; Isloor, Arun M.; Shetty, Prakash; Sook, Fun Pang (Elsevier, 2014)
A new series of N-[5-(4-(alkyl/aryl)-3-nitro-phenyl)-[1,3,4-thiadiazol-2-yl]-2,2-dimethyl-propionamide 4(ael) and 6-(4-Methoxy-phenyl)-2-(4-alkyl/aryl)-3-nitro-phenyl)-Imidazo [2,1-b] [1,3,4] thiadiazole 6(ael) were synthesized starting from 5-(4-Fluoro-3-nitro-phenyl)-[1,3,4] thiadiazole-2-ylamine. The synthesized compounds were characterized by IR, NMR, mass spectral and elemental analysis. All the compounds were tested for antibacterial and antifungal activities. The antimicrobial activities of the compounds were assessed by well plate method (zone of inhibition). Compounds 4a,4c and 6e,6g displayed appreciable activity at the concentration 0.5 - 1.0 mg/mL.